2023
DOI: 10.1200/jco.22.01997
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Placebo-Controlled Study of Olanzapine for Chemotherapy-Related Anorexia in Patients With Locally Advanced or Metastatic Gastric, Hepatopancreaticobiliary, and Lung Cancer

Abstract: PURPOSE Anorexia occurs in 30%-80% of patients with advanced malignancies, which may be worsened with chemotherapy. This trial assessed the efficacy of olanzapine in stimulating appetite and improving weight gain in patients receiving chemotherapy. METHODS Adults (≥18 years) with untreated, locally advanced, or metastatic gastric, hepatopancreaticobiliary (HPB), and lung cancers were randomly assigned (double-blind) to receive olanzapine (2.5 mg once a day for 12 weeks) or placebo along with chemotherapy. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Furthermore, mirtazapine had a positive effect in global health status at 8 weeks, HADS score, and functional scales, especially cognitive functioning, which could be inferred as a positive effect of better energy intake similar to the findings reported with olanzapine. 18 A multidisciplinary management including regular nutritional care in addition to the use of appetite stimulants like mirtazapine represents a crucial and revolutionary scheme of treatment for cancer-associated anorexia palliation. We suggest that therapeutic options to increase appetite, energy intake, and body weight need to be individualized according to catabolic state, muscle reserve, benefit and risk evaluation along with psychiatric and nutritional surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, mirtazapine had a positive effect in global health status at 8 weeks, HADS score, and functional scales, especially cognitive functioning, which could be inferred as a positive effect of better energy intake similar to the findings reported with olanzapine. 18 A multidisciplinary management including regular nutritional care in addition to the use of appetite stimulants like mirtazapine represents a crucial and revolutionary scheme of treatment for cancer-associated anorexia palliation. We suggest that therapeutic options to increase appetite, energy intake, and body weight need to be individualized according to catabolic state, muscle reserve, benefit and risk evaluation along with psychiatric and nutritional surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of this study, mirtazapine is a feasible and safe option to add as a nutritional intervention in patients with advanced NSCLC with anorexia given its benefit in energy intake including high-quality macronutrients, considering that increased energy intake is the first step to stop unintentional weight loss and stability or increase of body weight. Furthermore, mirtazapine had a positive effect in global health status at 8 weeks, HADS score, and functional scales, especially cognitive functioning, which could be inferred as a positive effect of better energy intake similar to the findings reported with olanzapine . A multidisciplinary management including regular nutritional care in addition to the use of appetite stimulants like mirtazapine represents a crucial and revolutionary scheme of treatment for cancer-associated anorexia palliation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, Sandhya and others conducted a randomized, double-blinded trial to test olanzapine. Smaller prior studies had suggested this agent, which is now used routinely to prevent chemotherapy-induced nausea and vomiting, would be effective for treating anorexia in patients with cancer 13▪▪ . Thus, these investigators enrolled 124 patients with gastrointestinal cancers and anorexia and randomly assigned each in a 1:1 manner to olanzapine 2.5 mg orally per day versus placebo.…”
Section: An Update On Palliation Of Anorexiamentioning
confidence: 99%
“…We thank Onishi et al 1 for their interest in our article. 2 The authors highlighted the problem of akathisia, a potential side effect of olanzapine. Studies of olanzapine as an antipsychotic agent (usual doses ranging from 10 to 20 mg once daily) have reported akathisia in 3%-16% of patients, 3 but these side effects are generally mild and rarely require treatment.…”
mentioning
confidence: 99%